Evaluation of anti-quorum sensing and antibiofilm effects of secondary metabolites from Gambeya lacourtiana (De Wild) Aubr. & Pellegr against selected pathogens - Rostan Mangoua Talla; Alfred Ngenge Tamfu; Brussine Nadège Kweka Wakeu; Ozgur Ceylan; Céline Djama Mbazoa; Gilbert Deccaux Wabo Fotso Kapche; Bruno Ndjakou Lenta; Norbert Sewald; Jean Wandji (BMC, 2023)
Abstract Background Microbial infections cause serious health problems especially with the rising antibiotic resistance which accounts for about 700,000 human deaths annually. Antibiotics which target bacterial death encounter microbial resistance with time, hence, there is an urgent need for the search of antimicrobial substances which target disruption of virulence factors such as biofilm and quorum sensing (QS) with selective pressure on the pathogens so as to avoid resistance. Methods Natural products are suitable leads for antimicrobial drugs that can inhibit bacterial biofilms and QS. Twenty compounds isolated from the medicinal plant Gambeya lacourtiana were evaluated for their antibiofilm and anti-quorum sensing effects against selected pathogenic bacteria. Results Most of the compounds inhibited violacein production in Chromobacterium violaceum CV12472 and the most active compound, Epicatechin had 100% inhibition at MIC (Minimal Inhibitory Concentration) and was the only compound to inhibit violacein production at MIC/8 with percentage inhibition of 17.2 ± 0.9%. Since the bacteria C. violaceum produces violacein while growing, the inhibition of the production of this pigment reflects the inhibition of signal production. Equally, some compounds inhibited violacein production by C. violaceum CV026 in the midst of an externally supplied acylhomoserine lactone, indicating that they disrupted signal molecule reception. Most of the compounds exhibited biofilm inhibition on Staphyloccocus aureus, Escherichia coli and Candida albicans and it was observed that the Gram-positive bacteria biofilm was most susceptible. The triterpenoids bearing carboxylic acid group, the ceramide and epicatechin were the most active compounds compared to others. Conclusion Since some of the compounds disrupted QS mediated processes in bacteria, it indicates that this plant is a source of antibiotics drugs that can reduce microbial resistance.